2015
DOI: 10.5713/ajas.13.0837
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Epigenetic and Meat Quality Related Genes in Fourteen Cattle Breeds and Association with Beef Quality and Carcass Traits

Abstract: Improvement for carcass traits related to beef quality is the key concern in beef production. Recent reports found that epigenetics mediates the interaction of individuals with environment and nutrition. The present study was designed to analyze the genetic effect of single nucleotide polymorphisms (SNPs) in seven epigenetic-related genes (DNMT1, DNMT3a, DNMT3b, DNMT3L, Ago1, Ago2, and HDAC5) and two meat quality candidate genes (CAPN1 and PRKAG3) on fourteen carcass traits related to beef quality in a Snow Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…These two transcripts were upregulated in families with a high whiteness index (Table 2 ). Previous studies showed that the DNA methylation gene, DNMT3a , was highly expressed in skeletal muscle and significantly associated with quality traits 110 112 . A single transcript encoding FBXO32 (Atrogin-1_ (GSONMT00031929001) and DE lncRNA Omy400042056, located within 1.3 kb, were positively correlated (R = 0.88; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…These two transcripts were upregulated in families with a high whiteness index (Table 2 ). Previous studies showed that the DNA methylation gene, DNMT3a , was highly expressed in skeletal muscle and significantly associated with quality traits 110 112 . A single transcript encoding FBXO32 (Atrogin-1_ (GSONMT00031929001) and DE lncRNA Omy400042056, located within 1.3 kb, were positively correlated (R = 0.88; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Nelore cattle, the ASAP1 gene (ArfGAP with SH3 domain, ankyrin repeat and PH domain 1) was located on the bovine Chr 14 where there are reports of QTLs for meat production traits (Tizioto et al, 2012). Liu et al (2015) studied 14 cattle breeds, including Simmental, for 16 SNPs of eight genes. They reported possible associations in the case of the Dragon Beef population.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic improvement of growth, carcass and meat quality traits is an important tool to evaluate the genetic merit of livestock. Recent reports found, that key traits such as growth and meat quality are dependent on many genes and affected by a variety of environmental factors and nutrition [Liu et al 2015, Ma et al 2015, Santiago et al 2017]. In the studies by Jahuey-Martinez et al [2016] five genes were identified as potential candidate for growth traits such as birth, weaning and yearling body weights in Charolais cattle [Jahuey-Martinez et al 2016].…”
Section: Discussionmentioning
confidence: 99%